Social Learning Theory dalam Pemodelan Pengembangan Wisata Embung Sarwadadi Kecamatan Talun Kabupaten Cirebon - Mukarto Siswoyo; Acep Komara; Dedi Muhammad Siddiq; Yandi Putra Pratama; Indah Lestari (Lembaga Penelitian Universitas Swadaya Gunung Jati, 2022)
Abstract. This paper aims to explore the tourism potential of the Sarwadadi reservoir lake located in Sarwadadi Village, Talun District, Cirebon Regency, and recommends a model for its development. Three models of reservoir development in the Special Region of Yogyakarta or Daerah Istimewa Yogyakarta (DIY), namely, Nglanggeran Reservoir, Tonogoro Reservoir and Langensari Reservoir are used as models. The research data were collected qualitatively by conducting interviews with the Head of Sarwadadi Village and two Sarwadadi community leaders and observations at the Sarwadadi Reservoir Lake location, as well as interviews with the managers of three reservoir lakes in DIY and observations at the three reservoirs. This research found that the partnership patterns between village, sub-district and district governments, village communities and civil society groups in the management of the Nglanggeran Reservoir Lake in DIY brings the Nglanggeran Reservoir Lake to be an exemplary model. Through the engagement of stakeholders of the Nglanggeran Reservoir in accordance to their main tasks and functions, Nglanggeran Reservoir’s managers are able to enhance the economic welfare of the local people. Keywords: Social Learning Theory; tourism development; Sarwadadi Reservoir Lake Abstrak. Paper ini bertujuan untuk mengeksplorasi potensi embung yang terletak di Desa Sarwadadi Kecamatan Talun Kabupaten Cirebon, serta merekomendasikan model pengembangannya. Tiga model pengembangan embung di Daerah Istimewa Yogyakarta (DIY), Embung Nglanggeran, Embung Tonogoro dan Embung Langensari dijadikan sebagai model. Data riset ini dikumpulkan secara kualitatif dengan melakukan wawancara kepada Kepala Desa Sarwadadi dan dua tokoh masyarakat Sarwadadi dan observasi ke lokasi Embung Sarwadadi, serta wawancara dengan pengelola tiga embung di DIY sekaligus observasi terhadap tiga lokasi embung tersebut. Riset ini menemukan bahwa pola kemitraan (partnership) antara pemerintah desa, kecamatan maupun kabupaten, masyarakat desa dan kelompok masyarakat civil (civil society group) dalam pengeloaan Embung Nglanggeran membawa Embung Nglanggeran sebagai model yang patut dicontoh. Dengan keterlekatan para stakeholder, pengelola Embung Nglanggeran berhasil membawa kesejahteraan ekonomi bagi warga sekitar. Kata kunci: Social Learning Theory; Pengembangan Wisata; Embung Sarwadadi.